Arrestin‐3‐Dependent Activation of c‐Jun N‐Terminal Kinases (JNKs). Issue 1 (2nd March 2015) - Zhan, Xuanzhi; Kook, Seunghyi; Kaoud, Tamer S.; Dalby, Kevin N.; Gurevich, Eugenia V.; Gurevich, Vsevolod V.
Abstract: Only one out of four mammalian arrestin subtypes, arrestin‐3, facilitates the activation of JNK family kinases. Here we describe two different protocols used for elucidating the mechanisms involved. One is based on reconstitution of signaling modules from purified proteins: arrestin‐3, MKK4, MKK7, JNK1, JNK2, and JNK3. The main advantage of this method is that it unambiguously establishes which effects are direct because only intended purified proteins are present in these assays. The key drawback is that the upstream‐most kinases of these cascades, ASK1 or other MAPKKKs, are not available in purified form, limiting reconstitution to incomplete two‐kinase modules. The other approach is used for analyzing the effects of arrestin‐3 on JNK activation in intact cells. In this case, signaling modules include ASK1 and/or other MAPKKKs. However, as every cell expresses thousands of different proteins their possible effects on the readout cannot be excluded. Nonetheless, the combination of in vitro reconstitution from purified proteins and cell‐based assays makes it possible to elucidate the mechanisms of arrestin‐3‐dependent activation of JNK family kinases. © 2015 by John Wiley & Sons, Inc.